"My life is not going to have any meaning." Personality and vulnerability to depression in Spanish youth. - López-Mora, Clara; González-Hernández, Juan (Anales de Psicología / Annals of Psychology, 2021)
Adolescents are a group at risk of developing depressive disorders, faced with a multitude of psychosocial circumstances and the resources available to meet vital needs. The risk of depression is associated with high avoidance of harm, low self-direction, and low persistence. The aim of the work was to explore the differences between different personality profiles between elements of the depressive process (presence of distress and absence of eustress) in adolescents. The presence of depression was evaluated through the Multicultural Inventory of Depression and personality through the Temperament and Character Questionnaire in a total of 229 participants, (n=121 males) (M age = 14.79; SD = 1.61). The exploratory cluster analyses showed the existence of 3 adolescent profiles based on temperament and character, being those adolescents with low persistence and self-transcendence, with high self-directedness, harm avoidance and rewards dependency who showed the highest indicators of depression. Specifically, significant differences were found in distress scores with adolescents in profile 3 having the highest indicators of state distress (F(224.4) = 21.73; p < .01) and trait (F(224.4) = 23.00; p < .01) with respect to adolescents in cluster 1 and cluster 2. In addition, they also had significantly lower scores on the indicators of eustrés state (F(224.4) = 11.59; p < .01) and trait (F(224.4) = 12.31; p < .01). The discussion focuses on the usefulness of Moscoso and Coninger's theories as frameworks for understanding the processes of acquisition, and risk of depression in adolescents.